How Diversity and Inclusion May Transform South African Commercial Property Organisations at Top Management Level - Motshegare, Reabetswe Regina (University of the Witwatersrand, Johannesburg, 2017)
The purpose of this report is to outline contemporary transformation frameworks that emphasise diversity and inclusion and how the latter may likely transform Growthpoint Properties South Africa (Growthpoint S.A). The main focus of the consultancy report is to compare and contrast traditional transformation methodologies and contemporary diversity and inclusion methodologies as strategies to assist Growthpoint S.A transform its senior and executive management. The propositions are that; an effective transformation strategy for Growthpoint S.A is one that focuses on identification; inclusion; attraction; diversification and retention of key talent at senior levels. Furthermore, that once diversity and inclusion interventions are implemented, there will be transformation at senior and executive levels. Out of 15 executives in the management team, six representatives were interviewed. The limitations highlight that the majority of participants are South African and may have certain biased perceptions about the topic as opposed to the rest of the participants, who are foreign nationals. The methodology focuses on a thematic analysis and four themes namely: leadership; corporate culture; strategies and communication are identified. Following in-depth discussions, six recommendations are provided. These include 360-degree feedback; diversity and inclusion workshops; introduction of a diversity and inclusion forum; KPI’s that measure diversity and inclusion targets; workplace enhancement programmes that focus on diverse candidates and lastly, robust succession plans. The role of the researcher as a professional Human Resource Business Partner ensured that any work dealt with is approached ethically, and the researcher’s ability to do this ensured quality, reliability, validity and effectiveness of the research.
A consultancy report submitted in partial fulfilment of the requirements for the degree of Master of Business Administration, to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2017.
Keywords: Diversity and inclusion; Exco members; Transformation; Growthpoint Properties; Leadership; Strategies; Corporate culture; UCTD; SDG-8: Decent work and economic growth; SDG-4: Quality education